Analysis of Stress Reduction following Yoga Exercise among Undergraduate Students of Physical Therapy - Soniha Aslam; Noman Ahmed; Javed Ali Memon (The Sky)
This experimental study aims to assess the effects of yoga exercises for the stress management of undergraduate students of Physical Therapy. Classes of yoga were conducted among physical therapy undergraduate students. Total of 30 participants male and female were selected through simple random technique and PSS-14 questionnaire was used to record the pre and post data of participants. Those students who were already diagnosed patients of any mental illness, taking anti-depressant medications, smokers, having any abnormality and had any recent surgery, were excluded from the study. Yoga training sessions were held for 6 weeks (3 time/weeks). Pre and post data were analyzed by SPSS version 23. The result shows that the pre yoga exercise Sessions mean value was 38.23 with a standard deviation of 2.918 and the post yoga exercise sessions mean value was 19.83 with a standard deviation of 6.735. The p-value was <0.05, indicating a highly significant difference. The results concluded that exercises were found to be effective in relieving the stress level and significant results were observed in students doing yoga exercises.